DEVELOPMENT NEEDS OF ENTREPRENEURIAL INTEREST IN YOUTH - Muksin . (UPT Penerbitan Universitas Jember)
Young generation are the group of people who are expected to become the successor and actor who contribute in solving society problems, among other issues related to economic welfare. Youth engagement in entrepreneurial activity becomes an important contributor in minimizing unemployment. Interest of youth towards entrepreneurship be the first step in building and developing businesses in the group. On the other hand there is a presumption that the young generation today is considered more interested in jobs outside of entrepreneurship, in particular the work as an employee in an organization. Based on these disparities, the study aims to: (a) analyze the perceptions and interests of youth on entrepreneurship, (b) analyze the factors related to interest youth in entrepreneurship, and (c) to analyze the needs of the youth entrepreneurship development. The writing method using a review of research results, which come from researchers themselves and other studies. The results showed: (i) There was variation in the perception and interests of youth on entrepreneurship, (ii) There are internal factors of youth and environment that relationship with the interest of entrepreneurship (iii) Development of interest of youth in entrepreneurship requires an integrated approach between formal, non-formal and informal learning.